Lot-to-lot consistency study of an Escherichia coli-produced bivalent human papillomavirus vaccine in adult women: a randomized trial. Issue 7 (2nd July 2020) - Su, Ying-Ying; Lin, Bi-Zhen; Zhao, Hui; Li, Juan; Lin, Zhi-Jie; Qiao, You-Lin; Wei, Li-Hui; Hu, Yue-Mei; Li, Rong-Cheng; Zhuang, Si-Jie; Sun, Guang; Zheng, Zi-Zheng; et al.
ABSTRACT: An Escherichia. coli -produced HPV-16/18 bivalent vaccine has been proved to be well-tolerated and highly efficacious against diseases associated with vaccine HPV types. As a part of the multi-center, randomized, double-blind phase III clinical trial, this lot-to-lot consistency study aimed to assess the safety and immunogenicity consistency of this novel HPV vaccine, which is also one of the objectives of the phase III trial. A total of 3689 healthy women aged 18–45 years were enrolled and randomly assigned 1:1:1 to three lots of the HPV vaccine groups. The primary outcomes were the IgG antibody level at 1 month after the last dose (month 7). In the immunogenicity per-protocol set (PPS), almost all of the participants seroconverted at month 7 and remained seropositive at month 42. For each paired comparison of the three lot groups, the two-sides of 90% CIs of GMC ratios for both IgG and neutralizing antibodies for HPV-16 and HPV-18 at month 7 were within the equivalence interval [0.5, 2]. Lot consistency was also demonstrated at month 42. The majority of recorded solicited reactions were mild or moderate. The incidences of solicited reactions of Lot 2 and Lot 3 were slightly higher than Lot 1. However, the incidences of solicited reactions of ≥ grade 3 and solicited reactions by symptoms were all similar among the three lot groups. None of the SAEs was considered related to vaccination by the investigator. In conclusion, this study demonstrates lot-to-lot consistency of the 3 consecutive lots of the E. coli -produced HPV-16/18 bivalent vaccine.